2021
DOI: 10.2147/jmdh.s312637
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Ethiopian Population to Receive COVID-19 Vaccine

Abstract: Background Despite efforts to decrease the burden, vaccine reluctance is increasing worldwide and hindering efforts to control the spread of COVID-19. Therefore, understanding the willingness of a community to receive a COVID-19 vaccine will help to develop and implement effective means of promoting COVID-19 vaccine uptake. Objectives This study was aimed to assess the willingness of the Ethiopian population to receive the COVID-19 vaccine and its determinant factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(146 citation statements)
references
References 21 publications
(32 reference statements)
9
129
8
Order By: Relevance
“… 46 This finding was consistent with the finding in South Africa, 47 Ethiopia (62.6%), 13 in the Arab world (62.4%). 20 The finding of the study was higher than the findings in Pakistan (37.80%), 42 Ethiopia (46.1%), 48 Ethiopia (31.4%), 49 16 countries across the continent (52.0%), 50 Nigeria (50.2%), 51 USA (36%), 52 Ethiopia (45.5%), 23 Turkey (29.2%). 53 On the contrary, it was lower than the finding in Canada (80.9%), 54 Mexico and India (80%), 50 China (91.3%), 36 Italy (67%), 55 low and middle-income countries (76.4%), 56 Colombia (77.0%), 57 India (78.6%), 28 India (79%), 44 Bangladesh (74.5%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“… 46 This finding was consistent with the finding in South Africa, 47 Ethiopia (62.6%), 13 in the Arab world (62.4%). 20 The finding of the study was higher than the findings in Pakistan (37.80%), 42 Ethiopia (46.1%), 48 Ethiopia (31.4%), 49 16 countries across the continent (52.0%), 50 Nigeria (50.2%), 51 USA (36%), 52 Ethiopia (45.5%), 23 Turkey (29.2%). 53 On the contrary, it was lower than the finding in Canada (80.9%), 54 Mexico and India (80%), 50 China (91.3%), 36 Italy (67%), 55 low and middle-income countries (76.4%), 56 Colombia (77.0%), 57 India (78.6%), 28 India (79%), 44 Bangladesh (74.5%).…”
Section: Discussionmentioning
confidence: 56%
“…This finding was higher than the study in Ethiopia (17.1%). 49 The possible reason for this variation may be due to the change in study period, variation in the target population.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two studies conducted during the same period of time (during the initiation of the immunization process in Uganda) showed considerably different rates of people's intention to receive the vaccine, with sufficiently lower rates observed in the population of medical students [100] 37.3%, compared with 70.1% observed among the general population. Studies conducted in Ethiopia during February [101] and February/March [102] report twice as large of a difference in vaccine acceptance rates among the general population(31.4% vs. 62.6%, respectively), while data obtained from specific parts of this country (North, Central, and South) are mainly in agreement (the acceptance rates are 45%on average).…”
Section: Resultsmentioning
confidence: 87%
“…Themes identified to contribute to high hesitancy were most prominently associated with certain socio-demographic variables. Such variables included income (e.g., being low-income population), age (e.g., younger patients were more hesitant, partially as they perceived being at lower risk compared to elders [ 69 , 74 , 79 , 80 , 96 , 149 ]), education (e.g., having a lower education degree [ 69 , 71 , 96 , 97 , 101 , 102 , 146 , 148 , 150 , 152 ]), area of residence (e.g., those in rural areas were more hesitant [ 69 , 101 , 149 ]), reported race and/or ethnicity (e.g., those who identified as minorities [ 38 , [69] , [70] , [71] , 75 , 77 , 78 , 103 , 149 , 151 ]). Interestingly, studies that included specific populations (such as patients with different health conditions) generally observed a lower intention to vaccinate among them compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this attempt, vaccine hesitancy and unwillingness to accept the COVID-19 vaccine is a challenge across the world [14].The unwillingness to accept the COVID-19 vaccine in Ethiopia is expected to be high. For instance, a study found that only 31.4% of the population were willing to take the COVID-19 vaccine [15]. Readiness to receive COVID-19 vaccine among professionals is also challenging; for example, only 27.7% of health care workers were intended to take COVID-19 in the Democratic Republic of the Congo.…”
Section: Introductionmentioning
confidence: 99%